ARTICULATORY ERRORS IN ARABIC SPEECH SOUNDS AND THEIR CAUSES FROM PHYSIOLOGICAL AND FIRST LANGUAGE BACKGROUND PERSPECTIVES - A. Dini Jumriana Adha; Tulus Musthofa; Indira Nur Annisa Budihardjo Putri; Muh. Naufal Fitra (Hijai - Journal on Arabic Language and Literature, 2026)
Background: Articulation errors remain a major challenge for Indonesian learners of Arabic due to differences in speech organ coordination and phonological systems. Purpose: The usual sections defined in a structured abstract are Background, Purpose, Methods, Results, and Conclusions. This paragraph should not be indented. Method: A qualitative Systematic Literature Review (SLR) was conducted by analyzing ten national and international journal articles on Arabic phonetics published between 2016 and 2024.. Results: Five error types were identified: substitution, omission, addition, distortion, and vowel duration errors. The most frequent errors involve pharyngeal, uvular, emphatic, and interdental sounds. These errors result from limited articulatory control and L1 phonological interference, which interact through reinforcement and error fossilization. Conclusion: Arabic pronunciation errors are shaped by physiological and linguistic factors; therefore, pronunciation instruction should integrate makhārij al-ḥurūf training with cross-linguistic phonemic awareness Keywords: articulation errors, physiological factors, mother tongue, phonological interference, Arabic phonetics.